Leptin Enhances Synthesis of Proinflammatory Mediators in Human Osteoarthritic Cartilage—Mediator Role of NO in Leptin-Induced PGE2, IL-6, and IL-8 Production - Katriina Vuolteenaho; Anna Koskinen; Meiju Kukkonen; Riina Nieminen; Unto Päivärinta; Teemu Moilanen; Eeva Moilanen (Mediators of Inflammation)
Obesity is an important risk factor for osteoarthritis (OA) in weight-bearing joints, but also in hand joints, pointing to an obesity-related metabolic factor that influences on the pathogenesis of OA. Leptin is an adipokine regulating energy balance, and it has recently been related also to arthritis and inflammation as a proinflammatory factor. In the present paper, the effects of leptin on human OA cartilage were studied. Leptin alone or in combination with IL-1 enhanced the expression of iNOS and COX-2, and production of NO, PGE2, IL-6, and IL-8. The results suggest that the effects of leptin are mediated through activation of transcription factor nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathway c-Jun NH2-terminal kinase (JNK). Interestingly, inhibition of leptin-induced NO production with a selective iNOS inhibitor 1400 W inhibited also the production of IL-6, IL-8, and PGE2, and this was reversed by exogenously added NO-donor SNAP, suggesting that the effects of leptin on IL-6, IL-8, and PGE2 production are dependent on NO. These findings support the idea of leptin as a factor enhancing the production of proinflammatory factors in OA cartilage and as an agent contributing to the obesity-associated increased risk for osteoarthritis.